A systematic review and gap analysis of drivers, impacts, and restoration options for abandoned croplands in Nepal. (September 2022) - Ojha, Roshan Babu; Atreya, Kishor; Kristiansen, Paul; Devkota, Deepa; Wilson, Brian
Abstract: Cropland abandonment is an emerging human-induced land use and is a growing national problem in Nepal. It is a key, current concern for local governance bodies and restoration options for this land are being actively sought. We initiated a systematic review of existing studies to identify the key causes and impacts of cropland abandonment and consider a range of restoration options. Data on the drivers, impacts, and restoration options for abandoned cropland were extracted from current relevant literature retrieved through four databases (Web of Science, Google Scholar, Scopus, and NepJol). Most studies focused on the drivers of cropland abandonment with less focus on the impacts and restoration options. Socio-economic drivers included outmigration, limited availability of labour or high labour cost, easy access to daily supply needs and high education level of the farming family members. Bio-physical factors were also reported as key drivers of cropland abandonment including unsuitable slope and rugged land topography, low soil fertility and low crop productivity. Both positive and negative impacts of cropland abandonment were also reported, principally bio-physical such as secondary vegetation succession as a positive impact and geomorphic damage and low crop production as negative impacts with a consequent decrease in food security. Most current studies focused principally on specific sites and typically lacked restoration options coordinated at a national level. Those studies that did identify restoration options for abandoned land suggested the adoption of short crop cycle, less labour-intensive crops, agro-forestry and conversion to pasture as key options. Most, however, failed to establish linkages between food insecurity, rural livelihoods, and ecosystem services after cropland is abandoned. As prior studies on abandoned land lack a defined study framework, we recommend an integrated research approach for Nepal. The approach suggests the need to adopt an integrated way for studying abandoned cropland restoration through the empirical analysis of local and national land abandonment issues. The proposed approach could also be applied in other areas where cropland abandonment is an issue. Highlights: Identifies the drivers of accelerating cropland abandonment and the impacts after abandonment. Highlights the importance of including various factors for integrated abandoned cropland studies. Proposes an integrated research approach with policy component for restoring abandoned cropland.